Performance of Routine Helicobacter pylori Invasive Tests in Patients with Dyspepsia - Hsi-Chang Lee; Ting-Chang Huang; Chin-Lin Lin; Kuan-Yang Chen; Chung-Kwe Wang; Deng-Chyang Wu (Gastroenterology Research and Practice)
Background. This study was designed to compare the accuracy of three different invasive methods for the detection of Helicobacter pylori (H. pylori) infection in patients with dyspepsia. These tests included culture, histology, and the rapid urease test (CLO test). Methods. H. pylori infection was diagnosed prospectively in 246 untreated dyspeptic patients who underwent upper gastrointestinal endoscopy. The gold standard for H. pylori infection was based on a positive culture or both a positive histological examination and a CLO test. Results. H. pylori was diagnosed in 33.3% of the patients. The sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy were as follows: histology from the antrum (95.12; 95.12; 90.7; 97.5; 95.12%); histology from the antrum and corpus (95.12; 95.12; 90.7; 97.5; 95.12%); histology from the corpus (76.83; 96.95; 92.65; 89.33; 90.24%); culture (91.46; 100; 100; 95.91; 97.15%); a CLO test from the antrum and corpus (85.59; 100; 100; 93.71; 95.52%); a CLO test from the antrum (64.63; 100; 100; 84.97; 88.21%); a CLO test from the corpus (69.51; 100; 100; 96.77; 89.83%), respectively. Conclusions. Antral biopsy histology and culture are the best methods for the diagnosis of H. pylori infection in our cohort of patients with dyspepsia.